An alternative angiosperm DGAT1 topology and potential motifs in the N-terminus - Winichayakul, Somrutai; Curran, Amy; Moraga, Roger; Cookson, Ruth; Xue, Hong; Crowther, Tracey; Roldan, Marissa; Bryan, Greg; Roberts, Nick (Frontiers in Plant Science, 2022)
The highly variable cytoplasmic N-terminus of the plant diacylglycerol acyltransferase 1 (DGAT1) has been shown to have roles in oligomerization as well as allostery; however, the biological significance of the variation within this region is not understood. Comparing the coding sequences over the variable N-termini revealed the Poaceae DGAT1s contain relatively high GC compositional gradients as well as numerous direct and inverted repeats in this region. Using a variety of reciprocal chimeric DGAT1s from angiosperms we show that related N-termini had similar effects (positive or negative) on the accumulation of the recombinant protein in Saccharomyces cerevisiae. When expressed in Camelina sativa seeds the recombinant proteins of specific chimeras elevated total lipid content of the seeds as well as increased seed size. In addition, we combine N- and C-terminal as well as internal tags with high pH membrane reformation, protease protection and differential permeabilization. This led us to conclude the C-terminus is in the ER lumen; this contradicts earlier reports of the cytoplasmic location of plant DGAT1 C-termini.